1999
DOI: 10.1128/iai.67.3.1461-1470.1999
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of a Pseudomonas aeruginosa Hybrid Outer Membrane Protein F-I Vaccine in Human Volunteers

Abstract: A hybrid protein [Met-Ala-(His)6OprF190–342-OprI21–83] consisting of the mature outer membrane protein I (OprI) and amino acids 190 to 342 of OprF of Pseudomonas aeruginosa was expressed in Escherichia coli and purified by Ni2+ chelate-affinity chromatography. After safety and pyrogenicity evaluations in animals, four groups of eight adult human volunteers were vaccinated intramuscularly three times at 4-week intervals and revaccinated 6 months later with either 500, 100, 50, or 20 μg of OprF-OprI adsorbed ont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Jones et al [16] showed in a clinical trial with burn patients immunized with a polyvalent P. aeruginosa LPS-based, T-cell-independent vaccine that overall survival of patients can be improved by vaccination immediately after a burn. However, in our study and also in the previously published vaccination trial in burn patients with native OPRs [18,19] it was possible to induce a primary T-cell-dependent immune response towards the vaccine in this group of patients. The elicited immune response was comparable to the secondary immune response against tetanus toxoid ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…Jones et al [16] showed in a clinical trial with burn patients immunized with a polyvalent P. aeruginosa LPS-based, T-cell-independent vaccine that overall survival of patients can be improved by vaccination immediately after a burn. However, in our study and also in the previously published vaccination trial in burn patients with native OPRs [18,19] it was possible to induce a primary T-cell-dependent immune response towards the vaccine in this group of patients. The elicited immune response was comparable to the secondary immune response against tetanus toxoid ( Figs.…”
Section: Discussionsupporting
confidence: 51%
“…Three brief episodes of fever (38. 23 8.4 ‡C) 24 h after a vaccination were recorded. Blood tests and physical examinations of the nasal mucosa, the deltoid muscle and general examinations remained unremarkable throughout the study.…”
Section: Tolerabilitymentioning
confidence: 99%
“…Despite advances in antimicrobial therapy, effective treatment and control of P. aeruginosa remains a persistent problem and a vaccine against P. aeruginosa would be a strategy to prevent infections with P. aeruginosa in immunocompetent susceptible patients [2][3][4][5]. Among various P. aeruginosa vaccine anti-gens, outer membrane protein F (OprF) has emerged as a viable candidate [2,[5][6][7][8][9]: (i) OprF is conserved antigenically in wild-type strains of P. aeruginosa [10]; (ii) OprF protein or DNA vaccines have been tested in animals and humans [11][12][13][14][15][16][17]; and (iii) OprF is involved in sensing of immune activation by binding to interferons (IFNs), which can be blocked effectively by vaccine-induced anti-OprF antibodies [18,19].…”
Section: Introductionmentioning
confidence: 99%